Analisis Literasi Keuangan dan Self Efficacy terhadap Personal Financial UMKM di Bangkalan Madura - Camelia, Nabila Putri; Sudarsono, Bambang; Kurniawan, Moh. Zaki (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The large number of MSMEs in Indonesia means that micro and medium scale businesses drive 60.51% of the economy, although it is not uncommon to find MSMEs who end up going out of business due to lack of financial management of their businesses. The conditions that occur in MSMEs in Indonesia are the focus of the problem in this research. Therefore, this research aims to examine and discuss the influence that the level of financial literacy and self-efficacy has on an individual's financial behavior. Along with the use of the purposive sampling method, the analysis used in this research is multiple linear regression analysis in the form of classic assumption tests, validity tests, reliability tests, hypothesis tests. In this research, it was found that financial literacy and self-efficacy have a significant influence on personal finance in MSMEs located in Bangkalan, Madura.